Curriculum Reform of Preschool Education Major in Universities: A Perspective from the Integration of Early Childhood Education and Care - Ren, Gaoru (Journal of Educational Research and Policies, 2026)
Under the background of the integration of early childhood education and care, there is an increasingly urgent demand for whole-cycle care and education for children aged 0-6. The cultivation of versatile professionals in “early childhood education and care” has become a key direction for the transformation of the preschool education major. Therefore, curriculum system reform serves as the critical approach for achieving this transformation. This study adopts a case study approach to analyze the talent training program and curriculum syllabi of the undergraduate preschool education major at N University, supplemented by interviews with faculty members. It aims to investigate the challenges encountered by the program in curriculum goal setting, curriculum structure design, the integration of childcare-related content, and the arrangements for practical courses. Finally, the study proposes a reform pathway for the curriculum system, which includes restructuring curriculum goals, adding childcare course modules, promoting the integration of childcare content, and strengthening practical courses.